Radiotherapy in Elderly Patients with Low-Risk Breast Cancer - Claudio Fuentes-Sánchez; María Elena García-Morales; Carmen González-San Segundo (Highlights on Medicine and Medical Research Vol. 12, 2021)
There have been few experiments on the treatment of elderly women with low-risk breast cancer. Although their clinical behaviour is similar to that of younger patients, there is a tendency to undertreat them, which may increase the risk of local relapses and reduce their survival. Even in low-risk patients, the rate of local recurrences after breast conserving surgery without adjuvant treatment (tamoxifen or radiotherapy) is high, approaching 20%, which is unacceptable. Despite the fact that tamoxifen and radiotherapy seem to have a similar impact in reducing local recurrence with similar overall survival, the combination of the two provides the best results with local relapses of less than 2%. Two studies that were designed specifically for elderly patients were published in recent years. Based on similar survival, these trials recommend omitting radiotherapy in patients with low-risk tumours treated with breast conserving surgery and tamoxifen, but with an increase in local relapses when radiotherapy is omitted, 10% at 10 years vs 2%. There is no evidence that tamoxifen treatment is less toxic in this group of patients who are typically poly-treated, and treatment compliance appears to be much lower than expected. This recommendation is highly contentious due to the reduction in the number of sessions in external radiotherapy with hypofractionation and the acceleration of partial breast irradiation, especially intraoperative radiotherapy with a single session. After breast conserving surgery, elderly patients may benefit from radiation therapy.